How do I look with my minds eye: perspective taking in social phobic imagery. - Wells, A; Clark, D; Ahmad, S (1998)
This study explored perspective taking in social phobics' images of past anxiety-provoking social situations and non-social situations. For images of social situations, social phobics were significantly more likely than non-patient controls to take an observer perspective, viewing themselves as if from an external point of view. In contrast, social phobics and controls did not differ in the perspective taken in images of non-social situations, which were generally viewed from a field perspective (seeing the situation as if looking out through their own eyes). The clinical significance of these findings is briefly discussed.